Child-Friendly Disaster Mitigation Education at Ar-Rahman Kindergarten, Tadukan Raga Village, Deli Serdang - Emilia Ramadhani; Dewi Kurniawati (Talenta Publisher, 2026)
Natural disasters are common in Indonesia and significantly impact all levels of society, especially children as a vulnerable group. This article aims to introduce the concept of disaster mitigation early to kindergarten children at TK Ar‑Rahman, Tadukan Raga Village, Deli Serdang Regency. The methods used include group- based learning with storytelling, educational songs, and disaster simulation. Results show improved preparedness: children became more alert, orderly, and capable of practicing self- rescue steps independently without panic. This activity has been proven effective in enhancing basic knowledge and skills in disaster situations, particularly earthquakes. It is recommended that such programs be conducted regularly and include teacher involvement to ensure knowledge and disaster-response behaviors are retained over the long term.